2018
DOI: 10.1021/acs.jpcc.8b02701
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Optical Forces by Single Particle Tracking in Slit-like Microfluidic Channels

Abstract: Optical trapping and manipulation techniques have attracted significant attention in various research fields. Optical forces divided into two terms, such as a scattering force and gradient one, work to push forward and attract objects, respectively. This is a typical property of optical forces. In particular, a tool known as optical tweezers can be created when a laser beam is converged at a focal point, causing strong forces to be generated so as to trap and manipulate small objects. In this study, we propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 52 publications
4
31
0
Order By: Relevance
“…The spot size is determined as the diameter at which the laser intensity becomes 1∕e 2 = 0.135 of the maximum. The temperature increase due to the laser irradiation with a similar optical setup used in our previous study (Nito et al 2018) was confirmed to be 1 K, and we consider the effect of temperature rise to be negligible. An excitation light is generated from a mercury lamp (U-HGLGPS, Olympus, Tokyo, Japan) thorough an excitation filter and irradiates the sample solution in the nanoslit device.…”
Section: Bonding Of Two Quartz Glasses Using Vacuum Ultra-violet Lightsupporting
confidence: 70%
See 4 more Smart Citations
“…The spot size is determined as the diameter at which the laser intensity becomes 1∕e 2 = 0.135 of the maximum. The temperature increase due to the laser irradiation with a similar optical setup used in our previous study (Nito et al 2018) was confirmed to be 1 K, and we consider the effect of temperature rise to be negligible. An excitation light is generated from a mercury lamp (U-HGLGPS, Olympus, Tokyo, Japan) thorough an excitation filter and irradiates the sample solution in the nanoslit device.…”
Section: Bonding Of Two Quartz Glasses Using Vacuum Ultra-violet Lightsupporting
confidence: 70%
“…Therefore, we expect that the scattering force in the z direction does not play a significant role in the particle motion for the case of d = 490 nm, and only the gradient forces should be taken into account. On the other hand, for the case of d = 190 nm, scattering force pushes the particles in the z direction, that is, the optically trapped particles stay close to the lid of the channel, as in the previous study (Nito et al 2018).…”
Section: Remark On Optical Forcessupporting
confidence: 54%
See 3 more Smart Citations